Pengaruh Latihan Passing Bawah melalui Media Dinding pada Ektrakulikuler Bola Voli SMA Negeri 1 Ayah Kabupaten Kebumen - Puput Widodo; Aldy Kurniawan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The results of observations at SMA Negeri 1 Ayah, Kebumen Regency showed that students had difficulty in mastering the technique of passing under the ball in volleyball. This study aims to measure the effect of training in passing under the ball through the wall media on the passing ability of under the ball students participating in extracurricular activities. This study used a